Suicide in Older Adult Men Is Not Related to a Personal History of Participation in Football - Iverson, Grant L.; Deep-Soboslay, Amy; Hyde, Thomas M.; Kleinman, Joel E.; Erskine, Brittany; Fisher-Hubbard, Amanda; deJong, Joyce L.; Castellani, Rudolph J. (Frontiers in Neurology, 2021)
Introduction: It is reasonable to estimate that tens of millions of men in the United States played high school football. There is societal concern that participation in football confers risk for later-in-life mental health problems. The purpose of this study is to examine whether there is an association between a personal history of playing high school football and death by suicide. Methods: The subjects were obtained from the Lieber Institute for Brain Development (LIBD) brain donation program in collaboration with the Office of the Medical Examiner at Western Michigan University Homer Stryker MD School of Medicine. Donor history was documented via medical records, mental health records, and telephone interviews with the next-of-kin. Results: The sample included 198 men aged 50 or older (median=65.0 years, interquartile range=57-75). There were 34.8% who participated in contact sports during high school (including football), and 29.8% participated in high school football. Approximately one-third of the sample had suicide as their manner of death (34.8%). There was no statistically significant difference in the proportions of suicide as a manner of death among those men with a personal history of playing football compared to men who did not play football or who did not play sports (p=.070, Odds Ratio, OR=0.537). Those who played football were significantly less likely to have a lifetime history of a suicide attempt (p=.012, OR=0.352). Men with mood disorders (p<.001, OR=10.712), substance use disorders (p<.020, OR=2.075), and those with a history of suicide ideation (p<.001, OR=8.038) or attempts (p<.001, OR=40.634) were more likely to have suicide as a manner of death. Moreover, those men with a family history of suicide were more likely to have prior suicide attempts (p=.031, OR=2.153) and to have completed suicide (p=.001, OR=2.927). Discussion: Suicide was related to well-established risk factors such as a personal history of a mood disorder, substance abuse disorder, prior suicide ideation, suicide attempts, and a family history of suicide attempts. This study adds to a steadily growing body of evidence suggesting that playing high school football is not associated with increased risk for suicidality or suicide during adulthood.